2016
DOI: 10.1590/0104-1428.2124
|View full text |Cite
|
Sign up to set email alerts
|

Curaua fiber reinforced high-density polyethylene composites: effect of impact modifier and fiber loading

Abstract: SbstractShort fibers are used in thermoplastic composites to increase their tensile and flexural resistance; however, it often decreases impact resistance. Composites with short vegetal fibers are not an exception to this behavior. The purpose of this work is to produce a vegetal fiber reinforced composite with improved tensile and impact resistance in relation to the polymer matrix. We used poly(ethylene-co-vinyl acetate), EVA, to recover the impact resistance of high density polyethylene, HDPE, reinforced wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 22 publications
(30 reference statements)
1
18
0
8
Order By: Relevance
“…8,15 The focus of these studies continues to be the extent to which lignocellulosic fibers can be used as reinforcing fillers instead of synthetic fibers. 9,[11][12][13]15,[17][18][19][20][21][22][23][24] For example, biocomposites composed of polyvinyl alcohol reinforced with cellulose microfibers isolated from biofuel industrial waste, Jatropha curcus L. seed shell were developed. Results showed that cellulose microfibers affected onset degradation temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…8,15 The focus of these studies continues to be the extent to which lignocellulosic fibers can be used as reinforcing fillers instead of synthetic fibers. 9,[11][12][13]15,[17][18][19][20][21][22][23][24] For example, biocomposites composed of polyvinyl alcohol reinforced with cellulose microfibers isolated from biofuel industrial waste, Jatropha curcus L. seed shell were developed. Results showed that cellulose microfibers affected onset degradation temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…This fiber is replacing glass and carbon fiber in some applications. Green materials gain attention for several applications from aerospace to the building industry because it combines some special features like low weight and price with good physical properties [1][2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…The green polymers appeared with an alternative to the plastic composites produced with substances derived from petroleum, in which the vegetal fibers make possible the obtaining of a material with physical and mechanical properties equal or similar to the EPS (Morais;Gadioli;Paoli, 2016;Fernandes et al, 2017;Xie et al, 2018), but with the advantage of being biodegradable (Landim et al, 2016). Thus, the use of coconut powder in the production of composites represents an innovative technological advance, because only a portion of the coconut shell is reused, after the consumption of water, in the manufacture of pots and substrate for production of seedlings.…”
Section: Introductionmentioning
confidence: 99%